Johanson-Blizzard syndrome. Report of a case and review of the literature - Sandra Montserrat Nájera-Villagrana; Armando Reyes-Cadena; Angélica León-Hernández (Instituto Nacional de Pediatría, 2014)
The Johanson-Blizzard syndrome is an autosomal recessive disease characterized by aplasia or hypoplasia of the wings of the nose, exocrine pancreatic insufficiency, hypothyroidism, dental abnormalities and mental retardation. There are fewer than 100 cases reported in the literature worldwide. We document the case of a girl with all the features of the Johanson-Blizzard syndrome, in order to facilitate its early recognition and anticipate the serious problems associated. Currently the patient is monitored by a multidisciplinary team from Instituto Nacional de Pediatría.